Optimal Controls for a Class of Impulsive Katugampola Fractional Differential Equations with Nonlocal Conditions - Xingru Chen; Haibo Gu; Yu Sun (Journal of Function Spaces)
In this paper, we investigate a class of impulsive Katugampola fractional differential equations with nonlocal conditions in a Banach space. First, by using a fixed-point theorem, we obtain the existence results for a class of impulsive Katugampola fractional differential equations. Secondly, we derive the sufficient conditions for optimal controls by building approximating minimizing sequences of functions twice.